Validitas Perangkat Pembelajaran Berbasis Education For Sustainable Development Pada Mata Pelajaran IPS Di Sekolah Menengah Pertama - Nasution, Nasution; Prasetyo, Ketut; Jacky, Muhammad (The Indonesian Journal of Social Studies, 2020)
This is a development research that aims to develop social studies learning tools based on Education for Sustainable Development (ESD) at the Middle School level. The results of this study are focused on the validity of the learning tools developed. The learning tools developed in this study are lesson plans, student teaching materials, student activity sheets, and social studies test questions sheets. This research is a type of development research using the 4D model. The results of this study are ESD-based social learning tools whose validity has been tested by experts.Â